2013
DOI: 10.3325/cmj.2013.54.157
|View full text |Cite
|
Sign up to set email alerts
|

Improving the intake of nutritious food in children aged 6-23 months in Wuyi County, China – a multi-method approach

Abstract: AimTo develop affordable, appropriate, and nutritious recipes based on local food resources and dietary practices that have the potential to improve infant feeding practices.MethodsWe carried out a mixed methods study following the World Health Organization’s evaluation guidelines on the promotion of child feeding. We recruited caregivers with children aged 6-23 months in Wuyi County, Hebei Province, China. The study included a 24-hour dietary recall survey, local food market survey, and development of a key l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
2
18
1
1
Order By: Relevance
“…Our analysis showed that eating meat was a protective factor of child anaemia; however, few caregivers gave meat to their children of this age due to the wrong beliefs that they could not digest meat. In addition, some caregivers did not know how to prepare meat for young infants, especially at the very beginning of complementary feeding,31 thus infant feeding counselling should include these specific issues to provide caregivers accurate knowledge and help them solve problems, such as demonstration of the preparation of meat instead of just giving information.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that eating meat was a protective factor of child anaemia; however, few caregivers gave meat to their children of this age due to the wrong beliefs that they could not digest meat. In addition, some caregivers did not know how to prepare meat for young infants, especially at the very beginning of complementary feeding,31 thus infant feeding counselling should include these specific issues to provide caregivers accurate knowledge and help them solve problems, such as demonstration of the preparation of meat instead of just giving information.…”
Section: Discussionmentioning
confidence: 99%
“…The restriction to studies published in English language, the small sample size in some of the observed intake studies, 23,31,38,42 and the fact that some studies sampled deliberately children from rural 22,29,31,32,[34][35][36]39,40 and/or poor communities 27,28,32,37,42 may raise questions on how representative the data from the observed intake studies are for usual dietary intakes of children in that specific country or region. In addition, the quality of some of the observed intake studies can be questioned since dietary assessment methods are generally recognized to be prone to biases.…”
Section: Discussionmentioning
confidence: 99%
“…The modeled intake studies modeled theoretical intakes or nutrient densities against recommended intakes or nutrient densities. Six [19][20][21][22][23][24] of the modeled intake studies used linear programming, a mathematical tool, that can be used among others to formulate optimized complementary feeding diets, which resemble current dietary practices as closely as possible while at the same time ensuring optimal nutrient intakes. 25 Details of the linear programming process and its challenges have been described before.…”
Section: Modeled Intake Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a logical sequence they cover a continuum of maternal, newborn, and child health topics. Chen et al and UNICEF's China office compare the quality of antenatal care in public and private sector in rural China (11), while Wu et al investigate approaches to improve the intake of nutritious foods in infants and young children (12). Jackson et al offer a series of meta-analyses to summarize the importance and contribution of different risk factors to severe episodes of acute lower respiratory infections (ALRI) (13).…”
mentioning
confidence: 99%